The Ghana Renal Registry – a first annual report - Boima, Vincent; Tannor, Elliott K; Osafo, Charlotte; Awuku, Yaw Asante; Mate-Kole, Michael; Davids, M Razeen; Adu, Dwomoa (African Journal of Nephrology, 2021)
There are few data on the treatment of kidney disease in sub-Saharan Africa and no formal reports of kidney replacement therapy (KRT) in Ghana. We report data from the newly established Ghana Renal Registry on the prevalence, causes, and modality of treatment of kidney disease in Ghana. Using the web-based data capture system of the African Renal Registry, data were obtained for patients who had KRT in Ghana between January and December 2017. A total of 201 patients started KRT, giving an incidence rate of 6.9 per million population (pmp). There were 687 patients on KRT, a prevalence rate of 23.6 pmp. The median age of prevalent patients was 45.5 years and 63.6% were male. Hypertensive kidney disease was the most common primary kidney disease, reported in 39.9%. The overwhelming majority of patients (96.2%) were treated with haemodialysis, 3.5% had a kidney transplant, and only two were on continuous ambulatory peritoneal dialysis. The incidence and prevalence of KRTtreated kidney failure in Ghana is low, and the patients are younger than those on KRT in high- and upper-middleincome countries. The major cause of kidney failure is hypertensive kidney disease and the vast majority of the patients are treated with haemodialysis.